Areas of harmonization of goal-setting in state programs of the Russian Federation on the example of the state program "Healthcare Development" - Y.Y. Shvets, S.N. Naumov, A.C. Martishina (International Journal of Advanced Science and Technology, 2020)
The article is devoted to the implementation and evaluation of state programs in Russia in the period from 2011 to 2017 as well as goal-setting of state programs up to 2024. Descriptive characteristics of programs and results of empirical analysis are presented. The interrelation between the level of implementation of state programs and the efficiency of certain activities is revealed. There is also a correlation between the socio-economic development and the achievement of program targets.